(3eHGOF GdGbJUGO GdLRFj (B/s - (3MOGO, efGhQ aQjMs; (3GdNWjH, MGRe HOQ s ((3EQHO(B: s (3OGQ GdCed(B, s, 1998)
(3eaGgje CSGSjI aj GdGbJUGO, fXQjI GdWdH hGdYQV,GdJhGRf(B-(3JaGYd GdWdH hGdYQV,GdeQhfI, fXQjI Sdhc GdeSJgdc,GdfXQjI GdMOjKI dSdhc GdeSJgdc(B((3efMfjGJ GdShGA(B)(3, fXQjI GdGfJGL hGdJcGdja, GdCShGb,Shb GdGMJcGQ GdJGe,GdefGaSI GdGMJcGQjI hGMJcGQ GdbdI,CSYGQ YfGUQ GdGfJGLs
(3cTGa GdeUWdMGJ U(B.295 (3HHdjhZQGajG U(B.314s
Keywords: (3GdGMJcGQs; (3GdGbJUGO GdLRFjs; (3GdGfJGLs